Mekanik ventile yoğun bakım hastalarında inspiratuar kas eğitiminin diafragma fonksiyonuna etkisinin radyolojik ve kardiyopulmoner değerlendirilmesi - Kaygusuz Benli, Reyhan (My University, 2023)
Amaç: Çalışmamızın amacı, ekstübasyon sonrası konvansiyonel fizyoterapi (KF)’ ye ek olarak uygulanan inspiratuar kas eğitimi (İKE) ‘nin diafragma yapı ve fonksiyonuna, abdominal duvar kas kalınlıklarına etkinliğini değerlendirmektir. Gereç ve Yöntem: Randomize kontrollü çalışmada 10 hastaya KF, 10 hastaya İKE+KF ekstubasyonu takiben 5 gün uygulandı. 10 sağlıklı kontrole İKE uygulandı. Müdahale öncesi ve sonrası diafragma ekskursiyonu (DE), inspirasyonda ve ekspirasyonda diafragma kalınlıkları ve kalınlaşma fraksiyonu ile diafragma pik kontraksiyon (PCV) ve relaksasyon hızı (PRV) ile internal oblik (IOA), eksternal oblik (EOA), transversus abdominus (TRA), rektus abdominis (RA) kas kalınlıkları ultrasonografi ile değerlendirildi. Solunum kas kuvvetini değerlendirmek için maksimum inpiratuar (MIP) ve maksimum ekspiratuar basınç (MEP) ölçüldü. Ayrıca Medical Research Council (MRC) ve yoğun bakımda fiziksel fonksiyon test bataryası (PFIT) ile kas kuvveti ve fiziksel fonksiyon değerlendirildi. Bulgular: Müdahale öncesine göre müdahale sonrasında diafragma kalınlıkları ve diafragma kalınlaşma fraksiyonunda istatistiksel anlamlı fark bulunmazken DE, PCV ve PRV’ de İKE+KF grubunda ve sağlıklı kontrollerde müdahale sonrasında arttı (p<0,05). Müdahale öncesine göre müdahale sonrasında KF grubunda abdominal kas kalınlıklarında fark bulunmazken İKE+KF grubunda İOA, EOA, RA kas kalınlıklarında ve sağlıklı grupta RA kas kalınlığında artış saptandı (p<0,05). Her 3 grupta da MIP değerinde müdahale öncesine göre artış ile sağlıklı ve İKE+KF grubunda MEP değerinde artış izlendi (p<0,05) IKE+KF ve KF grubunda MRC ve PFIT skorları müdahale öncesine göre istatistiksel anlamlı arttı (p<0,05). Sonuç: Mevcut bulgularımız ekstübasyon gününde başlayan İKE’ nin, MIP, MEP, DE, PCV, PRV ve İOA, EOA, RA kas kalınlıklarını anlamlı olarak iyileştirdiğini gösterdi. İnspiratuar Kas Eğitiminin, mekanik ventilasyon uygulanmış hastalarda ekstubasyon sürecini desteklediğini ve klinik pratikte rutin bir müdahale olması gerektiğini savunmaktayız.

Objective: The aim of our study was to evaluate the effects of Inspiratory Muscle Training (IMT) in addition to conventional physiotherapy (CP) on diaphragm structure and function, as well as abdominal wall muscle thickness, following extubation. Materials and Methods: In a randomized controlled trial, IMT was administered to 10 patients alongside CP, while CP alone was provided to another 10 patients for five days post-extubation. IMT was applied to 10 healthy controls. Diaphragmatic excursion (DE), diaphragm thickness at inspiration and expiration, diaphragm thickening fraction, peak diaphragmatic contraction (PCV), and relaxation velocity (PRV) were evaluated using ultrasonography. Additionally, the thickness of internal oblique(IOA), external oblique (EOA), transversus abdominis (TRA), and rectus abdominis (RA) muscles was measured. Maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP) were recorded. Muscle strength and physical function were assessed using the Medical Research Council (MRC) scale and Physical Function Test Batery in ICU (PFIT). Results: There was no statistically significant difference in diaphragm thickness or thickening fraction post-intervention. However, DE, PCV, and PRV increased post-intervention in the IMT+CP group and healthy controls (p<0,05). As compared to the CP group, IMT+CP showed an increase in IOA, EOA, and RA muscle thickness, while the healthy group noted an increase in RA muscle thickness (p<0,05). All three groups showed an increase in MIP post-intervention compared to pre-intervention, and an increase in MEP was observed in the healthy and IMT+CP groups (p<0,05). MRC and PFIT scores were significantly higher in the IMT+CP and CP groups post-intervention (p<0,05). Conclusion: Our findings indicate that IMT initiated on the extubation day significantly improved MIP, MEP, DE, PDC, PRV, and IOA, EOA, RA muscle thickness. We advocate that Inspiratory Muscle Training should be a routine intervention that supports the extubation process in mechanically ventilated patients.
Radiological and cardiopulmonary evaluation of the effect of inspiratory muscle training on diaphragm function in intensive care patients with mechanical ventilated
Keywords: cardiopulmonary physiotherapy; diafragma doku doppler görüntüleme Inspiratory muscle training; diafragma ultrasonu; diaphragm tissue doppler imaging; diaphragm ultrasound; Fizyoterapi; inspiratuar kas eğitimi; intensive care; kardiyopulmoner fizyoterapi; Physiotherapy; yoğun bakım